Effect of foliar application of boron trioxide and zinc oxide nanoparticles on leaves chemical composition, yield and fruit quality of Olea europaea L. cv. Picual - Genaidy, Esmail A. E. (2021)
The application of boron and zinc nanoparticles in different concentration was able to effect on the qualitative and quantitative characteristics of Picual cultivar in the first and second seasons, respectively, compared with the control treatment leaves mineral content and pigments, fruit set percent, fruit drop percent, fruits yield, fruit physical, and chemical characteristics. Moreover, spraying Picual cultivar with nano-boron at 20 ppm + nano-zinc at 200 ppm (T8) is the best treatment in this study to obtain the maximum final fruit set which led to harvest the maximum fruits yield with the high seed oil percentage and low acidity in the first and second seasons, respectively.